Formulasi dan Uji Aktivitas Perlindungan Tabir Surya Emulgel Ekstrak Etanol Kulit Bawang Merah (Allium cepa L.) secara In Vitro dan In Vivo - Vivin Nopiyanti; Lisa Wulandari; Suhartinah (CERATA Jurnal Ilmu Farmasi, 2021)
Sunscreen is a preparation used on the surface of the skin that works to absorb, scatter, or reflect ultraviolet light. Skin of red onion (Allium cepa L.) is one of the natural ingredients that can be used as sunscreen, especially the. Skin of red onion contains flavonoid and tannin compounds that have the potential as sunscreen. This study aims to find out the ethanol extract skin of red onion in the form of emulgel preparations that have good physical quality and stability, SPF value and sunscreen protection activities. Ethanol extract skin of red onion is obtained by maceration using 50% ethanol solvents. Emulgel ethanol extract skin of red onion is made in 4 formulas with variations in extract concentrations of 0,05% ; 0,1% and 0,2%. Emulgel preparations are carried out physical quality test, stability, determination of SPF value (Sun Protection Factor) in vitro using UV-Vis spectrophotometry. The SPF value is calculated by the Mansyur equation. The in vivo test used a male rabbit (New Zealand) were irradiated with a UV B exoterra lamp for 24 hours to see the resulting effects of erythema. The results showed that the onion peel ethanol extract emulgel had good quality and stability. Sunscreen protection tests in vitro and in vivo showed that the sunscreen protection activity met the requirements for the effectiveness of sunscreen with an SPF value of emulgel with a concentration of 0,05% ; 0,1% and 0,2% of 9,59 classified as protection extra, 21,14 and 35,85 were classified as ultra protected and the erythema score after 24 hours of UV exposure was 0.